Relationship between geomagnetic storms and occurrence of ionospheric irregularities in the west sector of Africa during the peak of the 24th solar cycle - Ondede, George Ochieng; Rabiu, A. B.; Okoh, Daniel; Baki, Paul; Olwendo, Joseph; Shiokawa, Kazuo; Otsuka, Yuichi (Frontiers in Astronomy and Space Sciences, 2022)
The study of ionospheric irregularities is important since many technological systems might be influenced by the ionosphere. In this work, we use data from the Global Navigation Satellite Systems (GNSS) receiver installed in Abuja, Nigeria, GPS Scintillation Network Decision Aid (SCINDA) TEC data from the Air Force Research Laboratory (AFRL) data archive, and the geomagnetic data from the World Data Center (WDC) in Kyoto, Japan, to investigate the relationship between geomagnetic storm and ionospheric irregularity occurrences using the rate of change of total electron content (TEC) index (ROTI), with a validation using the S4 indices, during the peak of the 24th solar cycle. The occurrences of irregularities were investigated on day-to-day and seasonal bases. The nighttime ionospheric irregularities, which are attributed to ionospheric plasma irregularities in the equatorial ionospheric F-region, were found to be prevalent. To investigate the relationship between the strength of ionospheric irregularities (ROTI) and the geomagnetic storm (Dst), the periodogram power spectral density (PSD) and regression analysis were used. The results showed that there was no correlation, cc = 0.073, between the Dst and ROTI, implying that the strengths of ionospheric irregularities occurring during geomagnetic storms are not strictly decided by the magnitudes of the storms; this was also confirmed using the S4 index. The impact of geomagnetic storms caused enhanced development or inhibition of ionospheric irregularities. We observed that the bulk of the storms occurring during the period of this study is not associated with ionospheric irregularities. Finally, the investigation showed that the correlation between the ROTI and Dst observed during the coronal mass ejection (CME)-driven geomagnetic storms was higher than that during the corotating interaction region (CIR)-driven geomagnetic storms, during the peak of the 24th solar cycle. The results of this work confirm the findings by other researchers.